Integration of Pianica Application as Interactive Media in Learning National Songs in Grade IV Elementary School - Rahmadhani, Renita Mila; Sa’diyah, Halimatus; Wijayanto, Wasis (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2025)
Introduction/Main Objectives: This study aims to characterize how well a digital pianica application, when integrated as an interactive learning tool, can improve learning interest, understanding of number notation, and the ability to play the national song